Morfemų ir žodžių akcentinė klasifikacija - Stundžia, Bonifacas (Kalbotyra, 1993)
1. When describing the accentual system of the Lithuanian language six accentual properties of morphemes can be distinguished: a) power, or accent (strong vs. weak, or accented vs. unaccented, morphemes depending on their ability to receive and keep stress in a paradigm); b) dominance (dominant vs. non-dominant affixal morphemes depending on their ability to have an influence upon the accentual properties of roots vs. stems); c) stress (stressed vs. unstressed morphemes, the latter being pretonic vs. posttonic ones); d) tone (circumflex vs. acute morphemes having a long stressed syllable); e) mutagenity (the property of some affixes resulting in prosodic, alternations in roots); f) attractibility (the property of some affixes resulting in the attraction of stress depending not on the accentual power of the root, but on the tone and quantity of the penultimate syllable).The relations of morphemes described on the basis of the first three accentual properties are at the very essence of the accentual system of each language with a morphemic accentual structure. The remaining three accentual properties are to be viewed as an supplementary characteristic of some morphemes. Tone plays a certain role in the choice of the accentual paradigm of a word, while mutagenity and attractibility are connected with the morphonological processes which either have no influence upon the relations based on the first three accentual, properties of morphemes (prosodic alternations), or violate these relations (the attraction or stress from a non-acute penultimate syllable).2. If the dominant strong morphemes are absent in the word, the stress falls on the first morpheme of the same or a larger accentual power.3. The accentual classification of primary words can be based on the linguistic and pragmatic factors that motivate the accentual power of roots.4. Derivatives can be classified accentually according to the main parts of speech taking into account the accentual properties of derivational formants or, more rarely, other affixes.5. Dominance, or at least an inclination towards it, is the most characteristic feature of derivational or, more rarely, non-derivational affixes of standard Lithuanian.6. The majority of the affixes of nominal derivatives are dominant, strong stressed suffixes and prefixes prevailing. Derivatives of weak dominant consonant suffixes and all the non-prefixal inflectional derivatives are characterised by rather regular circumflex metatony. The accentuation of nominal derivatives with prefixes is mostly predetermined by the accentual properties of the prefixes (the role of the accentual properties of flexions, suffixes and primary stems as will as the role of the derivational meaning is reduced to a minimum).7. The verb, on the contrary, is distinguished by non-dominant scanty affixes, i.e. accent-attracting prefixes and posttonic suffixes. The latter ones cause acute metatony, which is regular enough only for deverbative verbs (the inclination towards dominant stressed affixes is characteristic of the suffixes of denominative verbs).8. In word-form derivation, scanty dominant suffixes are characteristic of nominals while non-dominant ones are characteristic of verbs.